Antitumor activity of the dual PI3K/MTOR inhibitor, PF-04691502, in combination with radiation in head and neck cancer. Issue 3 (September 2017) - Tonlaar, Nathan; Galoforo, Sandra; Thibodeau, Bryan J.; Ahmed, Samreen; Wilson, Thomas G.; Yumpo Cardenas, Paola; Marples, Brian; Wilson, George D.
Abstract: Background and purpose: Head and neck squamous cell carcinoma (HNSCC) remains a clinical challenge where new treatments are required to supplement the current-standard-of care of concurrent chemoradiation. The PI3K/AKT/MTOR pathway has been identified from several next generation DNA sequencing studies to be commonly altered and activated in HNSCC. Material and methods: In this study we investigated the activity of PF-04691502, an orally active ATP-competitive, dual inhibitor of PI3K and mTOR, in combination with a clinically relevant fractionated radiation treatment in two contrasting, well characterized, low passage HNSCC models. Results: We found that PF-04691502 combined synergistically with radiation in the UT-SCC-14 model derived from a primary cancer but was ineffective in the UT-SCC-15 model which was derived from a nodal recurrence. Further examination of the status of key signaling pathways combined with next generation DNA sequencing of a panel of 160 cancer-associated genes revealed crucial differences between the two models that could account for the differential effect. The UT-SCC-15 cell line was characterized by a higher mutational burden, an excess of variants in the PI3K/AKT/MTOR pathway, increased constitutive activity of PI3K, AKT1 and 2 and MTOR and an inability to inhibit key phosphorylation events in response to the treatments. Conclusion: This study clearly highlights the promise of agents such as PF-04691502 in selected HNSCCs but also emphasizes the need for molecular characterization and alternative treatment strategies in non-responsive HNSCCs.